Analisis kandungan klorofil pada familia orchidaceae terhadap cekaman kekeringan - Intan Okta Nabilla; Endang Nurcahyani (Program Pascasarjana Universitas Papua, 2022)
Family Orchidaceae has 25.000 to 30.000 species which are divided into 5 subfamilies. Moon orchids and earth orchids are examples of plants from the Orchidaceae family. Orchid cooperatives in Indonesia have high economic value. In the cultivation of orchids, there are obstacles that occur, namely drought which can inhibit growth. Drought stress causes a slow increase in leaf area and affects stomata or photosynthesis which can reduce the speed of plant productivity. Drought stress control can be done by using superior varieties that are resistant to drought serum by adding a compound to the growing media. The purpose of the journal review is to determine the types of compounds that can be used for plants to be resistant to drought stress in the Orchidaceae family. The results of a review of several journals showed that PEG 6000 compounds and growth regulators (ZPT) could increase chlorophyll a, chlorophyll b and total chlorophyll in plantlets which decreased under drought stress conditions